Hijrat-e-Habāsha: A Role Model for the Muslim minorities in the promotion of Dialogue and Pluralism, In the contemporary Age - Dr. Hafiz Muhammad Farooq Abdullah; Dr. Hafiz Atif Iqbal (jihat-ul-islam, 2022)
Hijrat-e-Habāsha is much important in the Islamic history, which had a great impact on the Muslims and the Christian population of Abyssinia in various aspects. Abyssinia was a stable and vast state in the neighbourhood of Arabia. With whom the Quraish of Makkah had excellent relationships before Islam. Muslims migrated to Abyssinia due to the fair nature, honesty and good reputation of the ruler of Abyssinia, Najashi. Migration to Abyssinia indicates that Muslims can seek help and shelter from non-Muslims or non-Muslim states in order to preserve their religion or achieve legitimate interests. Due to the excellent foreign policy of the Prophet Muhammad (PBUH), the relations of Abyssinia were established with the state of Madinah instead of the polytheists of Mecca. From the migration to Abyssinia derives the salient rules and regulations and manners of Islamic diplomacy regarding relations with non-Muslim countries. The role of the Abyssinian refugees suggests that Muslim minorities in non-Muslim countries should play an organized and effective political role in order to achieve the promotion of Dialogue and Pluralism in the contemporary age. All these aspects will be covered in this paper.